Health care reforms and the crisis - Stamati, Furio; Baeten, Rita (Brussels, 2014)
" This report looks at the impact of the crisis on health care reform patterns in ten EU countries (France, Germany, Greece, Ireland, Italy, Lithuania, the Netherlands, Romania, Sweden and the UK-England). It assesses the changing allocation of responsibilities for regulation, financing, and provision of health care, as well as the growing influence of EU governance on national health systems.